Evaluation of fluvastatin in combination with the standard of care therapy (PEG-IFN/Ribavirin) in Egyptian patients with hepatitis C virus - Moataz S. Seyam,; Haitham A. Gabr,; Zakaria A. Salama,; Mohammed A. Mokhles,; Raghda N.Marzaban,; Ahmed F. Soliman, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Cholesterol biosynthesis suppresses the replication of HCV-1b replicons, thus influencing hepatitis C virus (HCV) natural history. This study aimed at comparing the efficacy and safety of fluvastatin (FLV) as an adjuvant therapy to the standard of care (SOC) therapy, i.e., pegylated interferon (PEG-IFN) and ribavirin, for the treatment of HCV patients. Materials and Methods: Sixty HCV patients were enrolled and allocated to either group I, who received the triple therapy (fluvastatin + SOC), or group II, who received SOC; the duration for both treatments was 48 weeks. All patients were subjected to pretreatment liver biopsy and monthly biochemical tests (liver profile, CBC), and quantitative HCV-RNA test was performed at weeks 0, 4, 12, 48, and 72. Results: All virological responses were higher in group I than in group II, with no statistical difference. Group I showed no manifestations of hepatotoxicity. Conclusion: Fluvastatin yielded a borderline, significantly higher complete early virological response than SOC; therefore, it is a safe adjuvant to the SOC therapy.